Gastric cancer risk is reduced by a predominance of antioxidant factors in the oxidative balance: a hospital-based case-control study in Korea - Jimi Kim; Jeonghee Lee; Il Ju Choi; Young-Il Kim; Jeongseon Kim (Epidemiology and Health, 2022)
OBJECTIVES Gastric carcinogenesis is linked to oxidative stress from both exogenous and endogenous exposures. This study aimed to determine the association between the risk of gastric cancer and the oxidative balance score (OBS), which comprises antioxidant and pro-oxidant factors, including diet and lifestyle. METHODS For this hospital-based case-control study, 808 controls and 404 patients with gastric cancer who had clinical records indicating Helicobacter pylori infection and the histological subtype of cancer were recruited. The OBS was determined based on diet and lifestyle factors obtained from a 106-item semiquantitative food frequency questionnaire and a constructed questionnaire. Logistic regression analysis was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). RESULTS A higher OBS was associated with a reduced gastric cancer risk (OR, 0.49; 95% CI T3 vs. T1, 0.33 to 0.71; p for trend <0.001). In a subgroup analysis, antioxidant factors showed inverse associations with gastric cancer risk (OR, 0.53; 95% CI T3 vs. T1, 0.35 to 0.79; p for trend=0.003). A stronger association with antioxidant factors was observed in patients with intestinal gastric cancer (OR, 0.34; 95% CI T3 vs. T1, 0.19 to 0.62; p for trend<0.001) and those with H. pylori infection (OR, 0.57; 95% CI T3 vs. T1, 0.37 to 0.88; p for trend=0.014). CONCLUSIONS A predominance of antioxidant factors compared to pro-oxidant factors from diet and lifestyle reduced the risk of gastric cancer. The combined effect of oxidative stress, which involves an altered balance between antioxidants and pro-oxidants, is important for modulating the risk of gastric cancer.